Energy management strategy of four-wheel drive SUV electric-hydraulic hybrid (EHH) power system based on optimal instantaneous efficiency. (August 2022) - Liao, Junzhang; Yang, Yang; Luo, Ronghua; Luo, Chang; Fu, Chunyun
Abstract: To address the problem of a large inrush current in pure electric vehicles under high-power driving and braking conditions, which damages the cycle life of the battery, a hydraulic auxiliary drive system is used to design a four-wheel-drive sport utility vehicle (SUV) electric–hydraulic hybrid(EHH) power system. Energy management strategy (EMS) research on this EHH power system is conducted. An EMS based on optimal instantaneous efficiency is proposed. The simulation results under the China light-duty vehicle test cycle for passenger car (CLTC-P) show that control effect of the EMS can improve by 3.27% than the EMS based on rule and achieve 97.43% of control effect of the dynamic programming(DP) global optimal EMS in terms of economic performance. Then the model predictive control (MPC) method is used, and the instantaneous efficiency optimal EMS is optimized. The simulation results under the CLTC-P show that the instantaneous efficiency optimal EMS optimized by MPC has an economic performance improvement of 1.13% compared with the performance before optimization. It can improve by 4.36% than the EMS RB and achieve 98.54% of control effect of the dynamic programming(DP) global optimal EMS in terms of economic performance.